Chinese Patients’ and Family Caregivers’ Perception of Care Quality, A Qualitative Study in Australian Hospitals - Ying Yu; Lily Xiao; Diane J. Chamberlain (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Cultural diversity in the Australian population is significant. It challenges health professionals in Australia's acute and critical care settings to provide culturally competent care for ethnic minority patients. Chinese Australians are the largest ethnic minority group in Australia. However, their experiences in acute hospital settings remain largely unknown. Studies on this patient group are much needed to address the research gap and add research evidence on transcultural nursing for the international community. The aim of this study was to explore Chinese patients’ and their family caregivers’ perceptions of care quality in Australian hospitals. A qualitative descriptive study design was used in this study. Adult Chinese patients born in mainland China and who had an acute and critical care admission were recruited from metropolitan hospitals in South Australia in 2019 using the snowball method. Semi-structured interviews were conducted in Mandarin. Data were transcribed verbatim in simplified Chinese for thematic analysis. Results were translated to English and checked by a bilingual team member. Ten participants participated in the study. Four main themes were identified from the data analysis: 1) the feeling of being disoriented in the ICU; 2) desire for comfort; 3) lack of engagement in treatment and care plans; and 4) lack of participation in quality improvement feedback to the care system. Chinese people have unique cultural beliefs, communication patterns, and health-seeking behaviors. To provide culturally competent care for acute and critically ill Chinese patients, health professionals are required to incorporate transcultural nursing theory, knowledge, skills, and attitudes into everyday practice.